Consultation générale et auditions publiques sur le projet de loi n° 60 - The English Speaking Catholic Council (ESCC) (2013)
Le Conseil catholique d'expression anglaise (CCEA) s’oppose à la charte proposée par le projet de loi 60, et ce, pour les raisons suivantes : • Il menace d’éroder, d’un point de vue historique et juridique, les libertés fondamentales de conscience, de religion, d’opinion et d’expression. Il s’agit des libertés « primordiales » dans notre société et il faut s’opposer à tout ce qui tend à diluer ou à réduire ces libertés. • Il propose une société sécularisée dans laquelle l’expression et la pratique religieuses sont marginalisées. Il cherche à recadrer le débat public de manière à ce que l’exercice des droits et libertés protégés par les chartes soit perçu comme imposé à la société et nécessitant la permission de l’État. • Il formule une notion embrouillée de la séparation de l’Église et de l’État en proposant que l’État a le pouvoir de définir la nature des croyances, de la pratique et de l’expression religieuses. • Dans tous les points susmentionnés, il situe le rôle de l’État au-dessus des paramètres de gouvernance appropriés d’un gouvernement élu démocratiquement et responsable. Le CCEA demande au gouvernement du Québec de retirer le projet de loi 60.

General Consultation and Public Hearings on Bill 60 - The English Speaking Catholic Council (ESCC) (2013)
The English Speaking Catholic Council (ESCC) objects to the proposed “Charter,” Bill 60, on the following grounds: • It threatens to erode the historically and legislatively foundational freedoms of conscience, religion, opinion and expression. These are considered to be “first” freedoms in our society and any trend to dilute or undermine these freedoms must be resisted. • It proposes a secularized society in which religious expression and practice are marginalized. It seeks to reframe the public discussion so that the exercising of Charter-protected rights is to be understood as an imposition upon society which requires the permission of the State. • It muddies the separation of Church and State as it proposes the State has the power to define the nature of religious belief, practice and expression. • In all of the aforementioned points the role of the State is elevated above the proper parameters of a democratically elected and responsible government. The ESCC calls upon the Government of Quebec to withdraw Bill 60.

Une réponse aux project de loi 60 : Loi n° 60, Charte affirmant les valeurs de laïcité et de neutralité religieuse de l’État ainsi que d’égalité entre les femmes et les hommes et encadrant les demandes d’accommodement - La Fédération québécoise des associations foyers-écoles (Quebec Federation of Home and School Associations (QFHSA), 2013)
La Fédération québécoise des associations foyers-écoles, Inc. (QFHSA) désire remercier la Commission des institutions de lui donner la possibilité de répondre au projet de loi 60. Ce projet de loi a été étudié de façon détaillée par notre Comité des droits et la réponse de la Fédération a été transmise par le conseil d’administration au nom de ses membres. La Fédération québécoise des associations foyers-écoles, Inc. s’oppose, dans son intégralité, au Projet de loi 60, une Charte affirmant les valeurs de laïcité et de neutralité religieuse de l’État ainsi que d’égalité entre les femmes et les hommes, et encadrant les demandes d’accommodement.

A Response to Bill 60 : Charter Affirming the Values of State Secularism and Religious Neutrality and of Equality Between Women and Men, and Providing a Framework for Accommodation Requests - Quebec Federation of Home and School Associations (QFHSA) (Quebec Federation of Home and School Associations (QFHSA), 2013)
Brief sent to The Committee on Institutions. The Quebec Federation of Home and School Associations Inc. (QFHSA) would like to thank the Committee on Institutions for the opportunity to respond to Bill 60. This Bill was studied in detail by the Rights Committee and the response of the Federation was passed by the Board of Directors on behalf of the membership. QFHSA is opposed, in its entirety, to Bill 60, a Charter affirming the values of State secularism and religious neutrality and of equality between women and men, and providing a framework for accommodation requests.

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2013)

English-speaking Seniors Unite to Create Provincial Vote - Seniors Action Quebec (2013)

QFHSA Fall Conference 2013 - Quebec Federation of Home and School Associations (QFHSA) (2013)

Bien vieillir dans sa langue, sa culture et sa communauté : soutien d'institutions fédérales clés et portrait des aînés anglophones du Québec - Canada. Office of the Commissioner of Official Languages (2013)
Cette étude exploratoire a deux grands objectifs. Le premier consiste à décrire le soutien qu’accorde le gouvernement fédéral au moyen de politiques et de programmes s’adressant aux aînés en général et aux aînés anglophones et francophones issus des communautés de langue officielle en situation minoritaire (CLOSM). Le deuxième objectif vise à brosser un portrait de la situation des aînés anglophones du Québec à l’aide de données. Pour ce faire, l’étude pose les questions suivantes : Où vivent les aînés anglophones du Québec? Qui sont-ils? Qui s’occupe d’eux? À quels services ont-ils accès, et comment utilisent-ils ces services? Nous espérons que l’étude aidera les CLOSM (y compris le nouvel organisme Aînés Action Québec, le réseau de défense des aînés anglophones de la province), à chercher du soutien des institutions fédérales.
Keywords: Official Language Minority Community (OLMC)

ELAN's Guy Rodgers Elected for Another Term on Culture Montréal Board - English Language Arts Network (ELAN) (2013)

Gender-based Approach to Women in Technology Project: Women in Technology : Final Report - Wood, Andrea (2013)
This paper represents the research component of a larger project focusing on “women in technology”, an initiative launched by YES Montreal in autumn 2012. The project strives to build capacity in Montreal’s technology sector by applying a gender-based analysis in the advocacy of women’s career development in the technology sector. The research will support the delivery of programs focusing on the development, implementation and evaluation of women’s careers in technology over a 3-year period, between 2013 and 2015.

Mémoire de L'Association des éditeurs de langue anglaise du Québec - Philpot, Robin (2013)

Au-delà du modèle unique : Des solutions distinctes pour des besoins distincts - Advisory Board on English Education (2013)
Dans le présent rapport à l’intention de la ministre, nous reprenons les thèmes et les préoccupations que nous avons exposés dans notre correspondance, nos rapports et nos mémoires antérieurs et qui décrivent encore aujourd’hui fidèlement la situation de l’éducation en langue anglaise au Québec. Nous y ajoutons des exemples actuels de préoccupations et de réussites afin de dresser un portrait à jour de la situation. Nous insistons sur le fait que nous n’avons nullement l’intention de promouvoir un système au détriment de l’autre, ni de désigner des fautifs. Selon nous, bon nombre des difficultés auxquelles font face les commissions scolaires, les écoles et les centres du secteur anglophone pourraient être amoindries si le MELS tenait davantage compte des différences entre les deux secteurs dans ses politiques et leur mise en oeuvre.

One Size Does Not Fit All: Distinct Solutions for Distinct Needs - Advisory Board on English Education (2013)
In this report to the Minister, the Advisory Board on English Education is taking the opportunity to review the themes and concerns identified in earlier correspondence, reports and briefs that continue to describe English education in Québec accurately, and to update them with current examples of both concerns and successes. We emphasize that there is no intention to promote one system over another, nor to assign fault. We believe that many of the inherent difficulties faced by English school boards, schools and centres could be mitigated if MELS were to take better account of the differences between the two sectors in its policies and their implementation. It is hoped that a description of the distinctiveness of the English sector and how it functions differently from the French sector will provide some insight as to how the English system is frequently constrained by many of the Ministry’s policies, especially in their application, and indicate the need for flexibility in implementing policy. This will ensure that the English education system can continue to prepare its graduates to participate fully in the life of Québec society.

Community Learning Centres : Changing Lives and Communities : Annual Report of Activities : September 2013 - Leading English Education and Resource Network (LEARN) (2013)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2013)

Language Training Program : Overall Profile 2009-2013 : Discussion Guide - Dialogue McGill (2013)

IALS and Essential Skills in Canadian Literacy Policy and Practice : A Descriptive Overview - Hayes, Brigid (2013)
The field of literacy encompasses many disciplines and areas of engagement from early childhood through schooling to community and work contexts over the lifespan. This review is concerned with a sub-set of the field – adult literacy – with a specific focus on the influence of the International Adult Literacy Survey (IALS) on policy and practice across Canada since its release in 1994. With the upcoming release of the Programme for the International Assessment of Adult Competencies (PIAAC) results in Fall 2013, this overview describes some of the ways IALS has been used by Canadian governments and literacy organizations.

Language Training Program : Overall Profile 2009-2013 - Dialogue McGill (2013)
The Language Training Program, Measure 1, has three components. The first two pertain to English and French for professional purposes courses offered through the regional language training projects designed and implemented by Quebec’s 18 health and social services agencies (the "agencies"). The third covers support activities for the trainers giving language courses in the regions and the learners who take those courses. These activities are developed and offered by the McGill Project team. The Program structure and content were developed by the McGill Project team and are described in Language Training Program – Frame of Reference 2009-2013, which also describes the target users; the Program objectives, partners and conditions; the parameters of the call for proposals for regional training projects; and regional allocation of the funding envelope. A coordinating mechanism, the MSSS-McGill Joint Committee, implements and monitors the Program, as prescribed in the Implementation Framework that the two organizations signed onto in November 2009.

Programme de Formation Linguistique : Profil global 2009-2013 - Dialogue McGill (2013)
Le Programme de formation linguistique, Mesure 1, comporte trois volets. Les deux premiers font référence à des cours d’anglais et de français, langue professionnelle, qui sont offerts dans le cadre des projets régionaux de formation linguistique conçus et mis en œuvre par les 18 agences de la santé et des services sociaux (les « agences »). Le troisième regroupe des activités de soutien destinées aux formateurs qui donnent des cours de langue en région et aux apprenants qui y participent. Ces activités sont développées et offertes par l'équipe du Projet McGill. La structure et le contenu du Programme ont été élaborés par l’équipe du Projet McGill et sont décrits dans le document Programme de formation linguistique - Cadre de référence 2010-2013, tout comme le sont la clientèle visée, ses objectifs, ses partenaires, les conditions à respecter, les paramètres de l’appel de propositions des projets régionaux de formation et la répartition régionale de l'enveloppe budgétaire. Un mécanisme de coordination, le Comité conjoint MSSS-McGill, assure la mise en œuvre et le suivi du Programme comme le prévoit le Cadre de mise en œuvre convenu entre les deux organisations, en novembre 2009.

Training and Retention of Health Professionals Project : Research development program : overall profile 2009-2013 - Dialogue McGill (2013)
The McGill University Training and Retention of Health Professionals Project (McGill Project) adds to the initiatives of the Government of Québec to give English-speaking Quebecers access to the full range of health and social services in their own language. It is an additional tool for implementing and revising regional programs for access to services in English, as prescribed in the Act respecting health services and social services. The McGill Project addresses the recognized needs of English-speaking communities and the challenge that those needs pose for Quebec's health and social services system. Given this, the McGill Project set up various programs to train and promote the hiring and retention of sufficient professionals qualified to deliver health and social services in English. The McGill Project is funded by Health Canada in the amount of $19 million over four years through its Official Languages Health Contribution Program (OLHCP). This report is the third in a three-part series to present the data gathered through the McGill Project from 2009 to 2013. The series deals with the three measures of the McGill Project, namely, the Language Training Program, the Retention and Distance Professional and Community Support Program, and the Research Development Program. The reports are organized to reflect the structure of each program as set out in the reference documents. Each report begins with an introduction of the program, then briefly describes the variables, data sources and sections of the report. This document reports on Measure 3, the Research Development Program, and is meant to inform Program reframing in Phase 3 (2013-2018).

Training and Retention of Health Professionals Project : Retention program : overall profile 2011-2013 - Dialogue McGill (2013)
The McGill University Training and Retention of Health Professionals Project (McGill Project) adds to the initiatives of the Government of Québec to give English-speaking Quebecers access to the full range of health and social services in their own language. It is an additional tool for implementing and revising regional programs for access to services in English, as prescribed in the Act respecting health services and social services . The McGill Project addresses the recognized needs of English-speaking communities and the challenge that those needs pose for Quebec's health and social services system. Given this, the McGill Project set up various programs to train and promote the hiring and retention of sufficient professionals qualified to deliver health and social This report is the second in a three-part series to present the data gathered through the McGill Project from 2009 to 2013. The series concerns the three measures of the McGill Project, namely, services in English. The McGill Project is funded by Health Canada in the amount of $19 million over four years through its Official Languages Health Contribution Program (OLHCP). the Language Training Program, the Retention and Distance Professional and Community Support Program, and the Research Development Program.

CRTC Must Oblige Vidéotron to Restore English-language Community Television Station - Quebec Community Groups Network (QCGN) (2013)

2013-2018 Strategic Plan - Quebec Community Groups Network (QCGN) (2013)
English-speaking Quebec is a diverse, confident, recognized and respected national linguistic minority that actively participates in and contributes to the social, economic, cultural and political life of Quebec and Canadian society.
Keywords: Official Language Minority Community (OLMC)

English-speaking Community Needs Formal Presence in Provincial Government, says QCGN members - Quebec Community Groups Network (QCGN) (2013)

Le Canada, le bilinguisme et le commerce - Arcand, Alan; Le Conference Board du Canada (Community Economic Development and Employment Corporation (CEDEC), 2013)
Le français est l’une des principales langues mondiales. Selon l’Organisation internationale de la francophonie (OIF), au moins 220 millions de personnes le parlent dans le monde1. C’est la langue officielle de tous les organismes des Nations unies et d’un grand nombre d’organisations internationales. Le français a pris naissance en France et s’est répandu grâce à l’expansion de ce pays outre-mer. Actuellement, quelque 30 pays dans le monde, dont le Canada, comptent le français parmi leurs langues officielles.

Canada, Bilingualism and Trade - Arcand, Alan; The Conference Board of Canada (Community Economic Development and Employment Corporation (CEDEC), 2013)
The French language is one of the world’s major languages. According to L’Organisation internationale de la Francophonie (OIF), at least 220 million people in the world speak French. It’s the official language of all United Nations agencies and a large number of international organizations. The language originated in France and spread by way of the country’s overseas expansion. Today, some 30 countries in the world, including Canada, have recognized French as an official language.

Canada, Bilingualism and Trade - Arcand, Alan; The Conference Board of Canada (Community Economic Development and Employment Corporation (CEDEC), 2013)
The French language is one of the world’s major languages. According to L’Organisation internationale de la Francophonie (OIF), at least 220 million people in the world speak French. It’s the official language of all United Nations agencies and a large number of international organizations. The language originated in France and spread by way of the country’s overseas expansion. Today, some 30 countries in the world, including Canada, have recognized French as an official language.

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2013)

CRTC Decision on CBC License Renewal Good News for English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2013)

Dawson Alternative School Presents : Dreams Broken or Otherwise - Dawson Alternative School (2013)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2013)

Allocution d’ouverture du QCGN devant la Commission de la culture et de l’éducation: Consultation générale et auditions publiques sur le projet de loi no 14 : Loi modifiant la Charte de la langue française, la Charte des droits et libertés de la personne et d’autres dispositions législatives - Quebec Community Groups Network (QCGN) (2013)

QCGN Opening Remarks to Committee on Culture and Education : General consultation and public hearings on Bill 14: An Act to Amend the Charter of the French Language, the Charter of Human Rights and Freedoms and Other Legislative Provisions - Quebec Community Groups Network (QCGN) (2013)

Quebec Federation of Home & School Association (QFHSA) Defends its Brief on Bill 14 Before the Quebec National Assembly - Quebec Federation of Home and School Associations (QFHSA) (2013)

Report : Community Network Forum : Enhancing Resiliency to Overcome the Challenges of Work and Personal Stress - Réseau de l’est de l’île pour les services en anglais (REISA) (2013)
A forum on approaches to promoting resilience to turn strengths into strategies to restore abilities to cope and adapt to stress in work and personal situations for ourselves and the communities we serve.

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2013)

Resolution re : Bill 14 - Donovan, Paul (2013)

Resolution re : Bill 14 - Donovan, Paul (2013)

Brief Submitted to the National Assembly of Quebec’s Committee on Culture and Education by the English Language Arts Network for the General Consultation and Public Hearings on Bill 14 : An Act to Amend the Charter of the French Language, the Charter of Human Rights and Freedoms and Other Legislative Provisions - English Language Arts Network (ELAN) (2013)
This brief was prepared by the English-Language Arts Network (ELAN), an incorporated not-for-profit organisation that represents 8,000 English-speaking artists in Quebec. ELAN is a meeting place for English-language artists and cultural workers of all disciplines from every region of Quebec, where they can share expertise and resources, build audiences and alliances, seek support, advocate for their interests, and make common cause with the Francophone arts community.

Brief Presented to the National Assembly’s Committee on Culture and Education with Regards to General Consultation and Public Hearings on Bill 14: An Act to Amend the Charter of the French Language, the Charter of Human Rights and Freedoms and Other Legislative Provisions - Quebec Community Groups Network (QCGN) (2013)
This brief was prepared by the Quebec Community Groups Network (QCGN), an incorporated not-for-profit organization that identifies, explores and addresses strategic issues affecting the development and vitality of English-speaking Quebec. The QCGN and its 41 members work cooperatively and in partnership with community stakeholders, leaders, governments and institutions, to advance the interests of our minority community.

Mémoire présenté à la Commission de la culture et de l’éducation de l’Assemblée nationale en regard à la consultation générale et auditions publiques sur le projet de loi n°14, Loi modifiant la Charte de la langue française, la Charte des droits et libertés de la personne et d’autres dispositions législatives - Quebec Community Groups Network (QCGN) (2013)
Ce mémoire a été rédigé par le Quebec Community Groups Network (QCGN), un organisme à but non lucratif dont la mission est de cerner, de clarifier et de traiter les enjeux stratégiques qui affectent le développement durable et la vitalité du Québec d’expression anglaise. Le QCGN et ses 41 organismes membres travaillent ensemble et avec les intervenants communautaires, les leaders, les gouvernements et les institutions, pour faire valoir les intérêts de notre communauté en situation minoritaire.

Baseline Data Report 2012-2013 : Quebec's English-speaking Community Networks and their Partners in Public Health and Social Services - Pocock, Joanne (Community Health and Social Services Network, 2013)
The 2012-2013 BDR reports unpon the nature and development of the partnerships that CHSSN Networking and Partnership Initiative (NPI) networks have established in their regions. The report represents the experience, thoughts, and observations - the collective wisdom - of the NPI networks on a range of topics related to their partnerships. The report looks back at the work incolved in partnering since the genesis of CHSSN, the ongoing challenges and successes, and the perceived impact of partnering on the NPI communities and their access to health and social services in English.
Keywords: Official Language Minority Community (OLMC)

A Brief Presented to the Parliamentary Committee on Cutlure and Education on Bill 14 (an Act to Amend the Charter of the French Language, the Charter of Human Rights and Freedoms and Other Legislative Provisions) - Quebec Federation of Home and School Associations (QFHSA) (2013)
On December 5, 2012, the Honorable Diane De Courcy, Minister responsible for the Charter of the French Language, introduced Bill 14, An Act to amend the Charter of the French Language, the Charter of Human Rights and Freedoms and other legislative provisions to the National Assembly. The decision to amend the Charter of the French Language and the Charter of Human Rights and Freedoms follows the recent minority win of the Parti Québécois in the National Assembly on September 4, 2012. QFHSA questions the need for this legislation when we are at a time of general peace in terms of language relations.

Un mémoire soumis à la commission Parlementaire de l’Assemblée Nationale sur le projet de loi 14 loi modifiant la charte de la langue française, la charte des droits et libertés de la personne et d’autres dispositions legislatives - Quebec Federation of Home and School Associations (QFHSA) (2013)
Le 5 décembre 2012, l’Honorable Diane De Courcy, ministre responsable de la Charte de la langue française, a déposé à l’Assemblée nationale le projet de loi 14, Loi modifiant la Charte de la langue française, la Charte des droits et libertés et d’autres dispositions législatives. La décision d’amender la Charte de la langue française et la Charte des droits et libertés suit la récente élection minoritaire du Parti québécois à l’Assemblée nationale, le 4 septembre 2012. La FQAFE s’interroge sur la nécessité d’une telle législation au moment où nous vivons une période plutôt paisible en matière de relations linguistiques.

QCGN Board of Directors : Resolution Regarding Bill 14, An Act to Amend the Charter of the French Language, the Charter of Human Rights and Freedoms and other Legislative Provisions, Tabled in the National Assembly of Quebec on December 5, 2012 - Quebec Community Groups Network (QCGN) (2013)

Improving Access to Health and Social Services for Quebec’s English-speaking Population : Development Priorities 2013-2018 - Udy, Michael; Howarth, Kelly; Kischuk, Nathalie; Medeiros, CMA (Community Health and Social Services Network (CHSSN), 2013)
This report has been prepared at the request of the Community Health and Social Services Network (CHSSN). It is intended for presentation to Health Canada in the context of the renewal of the Federal Government’s commitments to official language minority communities (OLMCs) for the period 2013-2018. The report presents development priorities for the improvement of access to health and social services in English for Quebec’s English-speaking communities as identified by the personnel of organizations work- ing on this issue.

Improving Access to Health and Social Services for Quebec’s English-speaking Population: Development Priorities 2013-2018 : A Companion Document - Udy, Michael; Howarth, Kelly; Kischuk, Nathalie; Medeiros, CMA (Community Health and Social Services Network (CHSSN), 2013)
This document has been prepared at the request of the Community Health and Social Service Network (CHSSN). It is the companion document to Improving Access to Health and Social Services for Quebec’s English- Speaking Population, Development Priorities 2013-2018, also prepared at the request of the CHSSN. Both are intended for presentation to Health Canada in the context of the renewal of the Federal Government’s com- mitments to official linguistic minorities for the period 2013-2018. These commitments have been funded to date under the Roadmap for Canada’s Linguistic Duality 2008-2013 (the Roadmap). More about the context of the project is presented in Appendix I.

English-speaking Seniors in Quebec - Canada. Office of the Commissioner of Official Languages (2013)

Les aînés anglophones au Québec - Canada. Office of the Commissioner of Official Languages (2013)

Community NetLink - Community Health and Social Services Network (CHSSN) (2013)

Les Québécois auraient besoin d’un nouveau contrat linguistique : Le rapiéçage, comme pour le projet de loi 14, est désuet / Quebecers Need a New Linguistic Social Contract : Piecemeal Approaches Like Bill 14 Are Outdated - D'andrea, Giuliano; Smith, Richard (2013)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2013)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2013)

Early Childhood Education : Successes and Challenges - Leading English Education and Resource Network (LEARN) (2013)

Teaching and Learning in the Digital World : Possibilities and Challenges - Leading English Education and Resource Network (LEARN) (2013)

Annual Activity Report : June 1, 2012 to May 31, 2013 - Literacy Quebec (LQ) (Literacy Quebec, 2013)

Annual Report / Rapport annuel 2012-2013 - Quebec Community Groups Network (QCGN) (2013)

Annual Report : 2012-2013 - Réseau de l’est de l’île pour les services en anglais (REISA) (2013)

Rapport Annuel : 2012-2013 - Réseau de l’est de l’île pour les services en anglais (REISA) (2013)

Biding Our Time with Rhymes - Writers in the Community (2013)